Краєзнавчі археологічні дослідження в Лугинському районі Житомирської області. Археологічна карта села Липники - Хоптинець, М.О. (Археологія і давня історія України, 2017)
Статтю присвячено історії дослідження Лугинщини і опису ново виявлених археологічних пам'яток села Липники та його околиць. За останні десятиліття на території села та навколо нього було відкрито десять нових різночасових археологічних пунктів, кожен з яких є по своєму цінним для науки. Археологічні дослідження краю проводилися у тісній співпраці місцевих краєзнавців та фахових археологів. В этой статье рассматривается история археологических исследований Лугинщины, а также представлены описания новых археологических памятников села Лыпники и его окрестностей. За последние десятилетия на территории села и вокруг него было открыто и изучено десять разновременных археологических пунктов, каждый из которых является по своему ценным для науки. Археологические исследования микрорегиона проводились в тесном сотрудничестве местных краеведов и профессиональных археологов. Такое сотрудничество очень продуктивно и открывает перспективы дальнейших исследований всего региона. In archaeology of Zhytomyr region Luhyny district was one of the least explored districts until recently. Local historians began to research this area in early 1990s and their discoveries caught the attention of professional archaeologists. As a result of their cooperation a number of archaeological sites (from the Paleolithic Age till the Late Middle Ages) were discovered and explored. This article focuses on the history of archaeological researches in Luhyny district and the description of the sites of the village Lypnyky and its suburb. Over the past decade there were ten sites discovered in the Lypnyky neighborhood. These sites belong to the various cultures from different periods and some of them are multilayered. This paper argues that the cooperation between archaeologists and local historians is essential and effective. Thus, the prospect for further researches of Lypnyky neighborhood, Luhyny district, and the entire region appears.